Wakatobi Native Bacteria Inhibit The Colony Growth of Alternaria porri and Fusarium oxyporum of Shallots in in Vitro Study - Gusti Ayu Kade Sutariati; Andi Khaeruni; Abdul Madiki (The Indonesian Phytopathological Society (Perhimpunan Fitopatologi Indonesia), 2020)
Wakatobi Native Bacteria Inhibit The Colony Growth of Alternaria porri and Fusarium oxyporum of Shallots in in Vitro Study Biological control of plant diseases based on the usage of microbes is important to reduce the use of chemical pesticides. The aim of this study was to determine the inhibitory and inhibitory mechanism in vitro of native endophytic bacterial isolates from Wakatobi as biological control of fusarium wilt and purple spots on shallot plants. The research was carried out at the Agronomy Unit of Agrotechnology Laboratory, Agriculture Faculty, Halu Oleo University Kendari. The research was aranged in a Completely Randomized Design (RAL), consisting of 9 treatments of endophytic bacterial isolates, namely Be03, Be02, Ke03, Ke05, Te01, Te05, Re05, Re05, and Wae05. The experiment was repeated 3 times wih 27 treatment units in total. The inhibitory test of endophytic bacteria on the tested pathogens was carried out in 2 steps, namely (1) against Alternaria porri and (2) Fusarium oxysporum. In addition to observing the inhibition mechanisme may involve. The ability of the endophytic bacteria isolates in producing HCN compounds was also tested. The results showed that endophytic bacteria had the ability to inhibit the growth of pathogenic fungi A. porri and F. oxysporum. Among the 9 isolates tested, there were 2 endophytic bacterial isolates which had the best ability to inhibit the growth of pathogenic A. porri and F.oxysporum fungi namely Te05 and Be03. Be03 isolates also have a high ability in producing HCN compounds, but no for Te05. Further research is needed to assay the effectiveness of those 2 isolates as biological control for diseases of shallot in a larger scale in the field.